Structuring the competencies for Knowledge Management Executive Program - Othman, Roslina; Noordin, Mohamad Fauzan; Jarjis, Junaiza (2008)
ROSLINA OTHMAN, MOHAMAD FAUZAN NOORDIN and JUNAIZA JARJIS: Structuring the Competencies for Knowledge Management Executive Program. In: Hawamdeh, S. et al. (eds.): KNOWLEDGE MANAGEMENT: Competencies and Professionalism. Proceedings of the 2008 International Conference on Knowledge Management. Ohio, USA, 23 – 24 October 2008. World Scientific, 2008 (pp 53-63) .